2012
DOI: 10.2215/cjn.05250511
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Levels and Trimestral Variation of Triiodothyronine and Thyroxine and Their Association with Mortality in Maintenance Hemodialysis Patients

Abstract: SummaryBackground and objectives Conflicting evidence exists with regard to the association of thyroid hormones and mortality in dialysis patients. This study assesses the association between basal and trimestral variation of thyroid stimulating hormone, triiodothyronine, and thyroxine and mortality.Design, setting, participants, & measurements In 210 prevalent hemodialysis patients, serum triiodothyronine, thyroxine, thyroid stimulating hormone, and interleukin-6 were measured 3 months apart. Cardiovascular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 35 publications
6
45
0
11
Order By: Relevance
“…Thyroid disorders including clinical and subclinical hypothyroidism in these patients can cause abnormalities in lipid metabolism, endothelial dysfunction, arterial stiffness, and inflammation contributing to the accelerated atherosclerosis and CVD (18)(19)(20)(21)(22). Similarly, data from clinical studies suggest that low levels of thyroid hormone may predict a higher risk of cardiovascular disease and overall mortality in patients with endstage renal disease (ESRD) undergoing dialysis (23,24). The causality of this association has not been elucidated and low thyroid hormone probably reflects an adaptive or maladaptive mechanism of chronic illness that characterizes CKD patients.…”
Section: Thyroid Disorders and Glomerular Filtration Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid disorders including clinical and subclinical hypothyroidism in these patients can cause abnormalities in lipid metabolism, endothelial dysfunction, arterial stiffness, and inflammation contributing to the accelerated atherosclerosis and CVD (18)(19)(20)(21)(22). Similarly, data from clinical studies suggest that low levels of thyroid hormone may predict a higher risk of cardiovascular disease and overall mortality in patients with endstage renal disease (ESRD) undergoing dialysis (23,24). The causality of this association has not been elucidated and low thyroid hormone probably reflects an adaptive or maladaptive mechanism of chronic illness that characterizes CKD patients.…”
Section: Thyroid Disorders and Glomerular Filtration Ratementioning
confidence: 99%
“…CVD is highly prevalent before initiation of dialysis due to several cardiovascular risk factors such as hypertension, dyslipidemia, endothelial dysfunction, arterial stiffness, and accelerated atherosclerosis. There is clinical evidence that subclinical or primary hypothyroidism and low T3 syndrome are strongly associated with CVD and mortality in the general population and in CKD patients (18)(19)(20)(21)(22)(23)(24). …”
Section: Associations Of Thyroid Disorders With Ckd and Cvdmentioning
confidence: 99%
“…Several studies have demonstrated that low T3 syndrome is associated with nutritional status, inflammation, and cardiomyopathy (6)(7)(8) as well as aortic stiffness in dialysis patients (9,10). In addition, a direct association between low T3 syndrome and all-cause and cardiovascular (CV) mortality has been reported in patients with CKD (11) and hemodialysis (HD) patients (8,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing body of evidence suggests that low T3 is associated with decreased systolic function, increased left ventricular mass, endothelial dysfunction, atherosclerosis, vascular calcification, and altered ventricular conduction in patients on dialysis (Table 1) (9)(10)(11)(12). Moreover, some but not all studies have shown that low T3 levels are associated with higher all-cause and cardiovascular mortality in this population (4,13).…”
mentioning
confidence: 99%
“…First, given that T3 was measured at a single point in time, analyses did not account for changes in thyroid hormone status over time. To date, only two studies of thyroid function and mortality have examined repeated measures of thyroid functional tests in patients on dialysis (i.e., Meuwese et al [13] examined T3 levels at baseline and 3-month follow-up, and Rhee et al [16] examined time-varying TSH), and additional study of time-varying T3 levels may advance our understanding of the short-term implications of thyroid hormone deficiency in this population. A second limitation is the assumption that circulating T3 levels reflect hormone concentrations at the Table 1 cardiac tissue level; however, a more sensitive and specific metric for intracardiac thyroid hormone signaling has not yet been identified (7).…”
mentioning
confidence: 99%